Efeito do aquecimento e da disponibilidade de recursos provenientes de detritos sobre a microbiota aquática. - Silva, Melissa Progênio da (2021)
Freshwater environments are the most vulnerable to climate change, and projected increases in temperature over the coming decades bring an unfavorable scenario for aquatic organisms. Warming, when combined with nutrient availability, can trigger even more complex interactions in the functioning of microbial food webs. The aim of this study was to evaluate the influence of warming and resource availability from detritus on the community structure of freshwater aquatic microbiota (richness, density and beta diversity) using natural microcosms (tank bromeliads) as a model system. Warming was simulated with temperature increase projections for the next decades following the Intergovernmental Panel on Climate Change. The dry mass (g) of coarse particulate organic matter (CPOM) from each bromeliad was used as a measure for resource availability (detritus biomass). Detritus biomass caused a negative effect on algal and microfauna density, and for total algal richness. Detritus biomass explained the variation for almost all components of microfauna beta diversity, except for the replacement component (βrepl), where warming was responsible for this variation. For algae the interaction between warming and detritus biomass was most important in explaining the variation in total beta and βrepl, while for the richness difference component (βrich) this variation was explained only by detritus biomass. In summary, the results obtained suggest that warming and increased detritus biomass acted strongly on the structuring of the communities, reducing the density and richness of the aquatic microbiota. Furthermore, the results provide evidence that temperature can increase the dissimilarity of communities of groups of organisms in the heterotrophic plot (microfauna), mainly by species substitution.